CO2 Laser irradiation of GeO2 planar waveguide fabricated by rf-sputtering - Chiasera, A. (2013)
GeO2 transparent glass ceramic planar waveguides were fabricated by a RF-sputtering technique and then irradiated by a pulsed CO2 laser. The effects of CO2 laser processing on the optical and structural properties of the waveguides were evaluated by different techniques including m-line, micro-Raman spectroscopy, atomic force microscopy, and positron annihilation spectroscopy. After laser annealing, an increase of the refractive index of approximately 0.04 at 1.5 μm and a decrease of the attenuation coefficient from 0.9 to 0.5 db/cm at 1.5 μm was observed. Raman spectroscopy and microscopy results put in evidence that the system embeds GeO2 nanocrystals and their phase varies with the irradiation time. Moreover, positron annihilation spectroscopy was used to study the depth profiling of the as prepared and laser annealed samples. The obtained results yielded information on the structural changes produced after the irradiation process inside the waveguiding films of approximately 1 μm thickness. In addition, a density value of the amorphous GeO2 samples was evaluated.